Experimental evaluation on a Mach-scaled SNUF blade for active vibration control - Im, B.U.; Lee, C.B.; Shin, S.J. (My University, 2019)
Seoul National University Flap (SNUF) blade equipped with an active trailing-edge flap is fabricated and tested under static conditions. Bench tests on the flap mechanism reveal the control authority and endurance of the devised flap actuation mechanism while centrifugal load acts on the flap. Also, the frequency response of the flap mechanism is identified where the static load is imposed on the flap. Blade tensile tests are performed for each root and flap component separately. Each specimen shows greater than 40% of safety margin compared with the expected maximum centrifugal load from comprehensive rotor analysis. The axial stiffness estimated from the measured skin strain is in good agreement with the cross-sectional analysis. Basic properties tests on the fabricated blade are carried out. Both sectional strain measurements and the identified modal frequencies show similar discrepancies in the flapping and torsional directions, which are 4% and 20% differences with design analysis, respectively. Finally, estimated MAC values for the first three fundamental modes satisfy the rejection criteria of 0.9.